2003
DOI: 10.1124/jpet.103.053900
|View full text |Cite
|
Sign up to set email alerts
|

Mediation of β-Endorphin by Isoferulic Acid to Lower Plasma Glucose in Streptozotocin-Induced Diabetic Rats

Abstract: We investigated the mechanism(s) by which isoferulic acid lowers plasma glucose levels in streptozotocin-induced diabetic rats (STZ-diabetic rats). In STZ-diabetic rats, isoferulic acid dose dependently lowered plasma glucose concentrations and increased plasma ␤-endorphin-like immunoreactivity (BER). Both of these effects of isoferulic acid were abolished by pretreatment of rats with tamsulosin or 2-[2,6-dimethoxyphenoxyethyl]aminomethyl-1,4-benzodioxane hydrochloride (WB 4101) at doses sufficient to block ␣ … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 40 publications
(30 citation statements)
references
References 28 publications
1
29
0
Order By: Relevance
“…It has been recently reported that isoferulic acid exhibits antihyperglycemic activity in streptozotocin (STZ)-induced diabetic rats 7 . It activates  1 -adrenoceptors to enhance the secretion of -endorphin, which stimulates the opioid -receptors to increase glucose use and/or reduce hepatic gluconeogenesis, resulting in a reduction of the plasma glucose concentration 23 . Our previous studies demonstrated that ferulic acid, but not isoferulic acid, directly stimulates insulin secretion from the pancreas, leading to decreased plasma glucose concentrations in rats 24 .…”
Section: Discussionmentioning
confidence: 99%
“…It has been recently reported that isoferulic acid exhibits antihyperglycemic activity in streptozotocin (STZ)-induced diabetic rats 7 . It activates  1 -adrenoceptors to enhance the secretion of -endorphin, which stimulates the opioid -receptors to increase glucose use and/or reduce hepatic gluconeogenesis, resulting in a reduction of the plasma glucose concentration 23 . Our previous studies demonstrated that ferulic acid, but not isoferulic acid, directly stimulates insulin secretion from the pancreas, leading to decreased plasma glucose concentrations in rats 24 .…”
Section: Discussionmentioning
confidence: 99%
“…Considering that isoferulic acid has a strong hypoglycemic activity [1821], the isoflavones were esterified with acetyl isoferulic acid. This structural modification was expected to improve their efficacy through possible synergy.…”
Section: Methodsmentioning
confidence: 99%
“…Our data cannot elucidate if it could be direct or indirect, probably mediated by the effect of other still unknown factors, and if such action could be carried out at the receptorial level or in the intracellular enzymatic pathways. In this concern, some investigators tried to identify the role of µ, δ and the recently isolated σ opiates receptors in the liver of rats [53,54], but further studies are needed to throw light in this field.…”
Section: Physio-pathologic Mechanisms Of Naltrexone Metabolic Actionmentioning
confidence: 98%